Empowering teachers: implementing the Tut Wuri Handayani supervision model to enhance teacher competence - Simanjuntak, Rivai M.; Milfayetty, Sri; Darwin, Darwin (Institute of Advanced Engineering and Science, 2024)
An inspiring supervision model based on the Tut Wuri Handayani concept, with a research and development (R&D) approach that refers to the Borg and Gall model, has been successfully developed. Through a comprehensive investigation, this study aims to bolster the competence and effectiveness of teachers. Model feasibility evaluation was carried out by two model design experts, with an average ideal percentage value of 86.2% (outstanding assessment and feasibility categories). Model feasibility evaluation was carried out by two model design experts and two content design experts. The average ideal percentage value given by model design experts was 86.2% (outstanding assessment and feasibility categories), while that given by content design experts was 76.64% (outstanding service and feasibility categories). Based on the test for model users three times, t-test data was obtained for a small group between commitment and competence, fighting power and competence, and religion and competence, showing tcount>ttable, respectively. The t-test results for the medium and large groups also show tcount>ttable. The dataset analysis shows that the inspiring supervision model based on Tut Wuri Handayani is practical and feasible. This research sheds light on the positive impact of implementing the Tut Wuri Handayani supervision model for enhancing teacher competence and, consequently, improving the quality of the learning process.